2018
DOI: 10.1186/s12936-018-2183-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of individual and community-level bed net usage on malaria prevalence among under-fives in the Democratic Republic of Congo

Abstract: BackgroundUnderstanding the contribution of community-level long-lasting, insecticidal net (LLIN) coverage to malaria control is critical to planning and assessing intervention campaigns. The Democratic Republic of Congo (DRC), which has one of the highest burdens of malaria cases and deaths and has dramatically scaled up LLIN ownership in recent years thus it is an ideal setting to evaluate the effect of individual versus community-level use to prevent malaria among children under the age of 5.ResultsData wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 28 publications
7
67
2
1
Order By: Relevance
“…These studies showed that increasing age, wealth, and individual bed-net use are protective, as are increasing community level bed-net use, lower average temperature and higher altitude [9][10][11][12] . However, these studies included only children under the age of five 9,10 , or were small and geographically limited 11,12 . A study of adults in the DRC conducted using data from the 2007 DHS identified several risk factors, such as younger age, male sex, and lower individual and community level wealth 13 ; however, no nationally representative risk factor studies of adults have been conducted since.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed that increasing age, wealth, and individual bed-net use are protective, as are increasing community level bed-net use, lower average temperature and higher altitude [9][10][11][12] . However, these studies included only children under the age of five 9,10 , or were small and geographically limited 11,12 . A study of adults in the DRC conducted using data from the 2007 DHS identified several risk factors, such as younger age, male sex, and lower individual and community level wealth 13 ; however, no nationally representative risk factor studies of adults have been conducted since.…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies performed in the DRC have identified important risk factors for infection 4,9,10 . These studies showed that increasing age, wealth, and individual bed-net use are protective, as are increasing community level bed-net use, lower average temperature and higher altitude [9][10][11][12] . However, these studies included only children under the age of five 9,10 , or were small and geographically limited 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods of the malaria vector control in Cameroon is the use of mosquito bed nets and depending on whether it is a long-lasting insecticidal one, further increases the vector control chances. Several studies have highlighted the importance of increased mosquito net usage and LLITN and their role in reducing the incidence of malaria in SSA (38)(39)(40)(41)(42)(43)(44). In this study, most urban-city centers and rural clusters household settlements in the North region had at least one mosquito net whether or not it was a treated (> 50% ), while the West and East regions recorded a low coverage for the above ITNs coverage category.…”
Section: Discussionmentioning
confidence: 79%
“…In DRC, studies from 2013 have shown no significant difference in the odds of malaria infection between people owning a permethrin LLIN and those without a net, while those with deltamethrinand alpha-cypermethrin-treated nets had significantly reduced odds of malaria infection [16,17].…”
Section: Introductionmentioning
confidence: 99%